Keanekaragaman buah Pandan tikar (Pandanus tectorius Park.) asal Provinsi Papua dan Provinsi Papua Barat berdasarkan karakteristik fisik dan kandungan gizinya - Sarungallo, Zita; Hegemur, Katarina; Susanti, Cicilia Maria Erna; Sinaga, Nurhaidah Iriany; Djading, Abadi; Irbayanti, Diana Nurini (Program Pascasarjana Universitas Papua, 2025)
ABSTRACT : The Pandan tikar (Pandanus tectorius Park.) was found in many coastal areas, has the potential to be processed into various food products. This study aims to study the diversity of 6 Pandan tikar fruits originating from several locations of Papua and West Papua province based on their physical characteristics and nutritional content. The method used in this study is an exploration method with observations. The origins of the six Pandan tikar fruits were Mansinam (P1), Mansinam (P2), Pasir Putih (P3), Arboretum Fahutan (P4), Hamadi (P5), and Kampung Wardo (P6). The results of this study indicate that the 6 fruits of Pandan tikar observed have a varied shape, namely ovoid (P1 and P2), ellipsoidal (P3), sub-globose (P4 and P6), and globose (P5); with variations in the colour of the fruit flesh, namely yellow (P1, P2, P3, P4), orange (P5), and red (P6). Fruit size dimensions varied; with whole fruit weight 1.8-6.0 kg, length 19.0-23.3 and width 15.0-25.3 cm, fruit circumference of 56-80.5 cm. The total weight of phalange was 1.6-5.75 kg/fruit with a total of 45-152 phalange/fruit, the width and weight of phalange were 3.2-4.5 cm and 24.8-53.8 g/fruit, respectively; while the weight of edible part was 6-21 g/phalange, and the percentage of edible part was 28.0-39.4%/fruit. Total soluble solids (TSS) 3.3-7.2°Brix and vitamin C 4.8-44.1 mL/100g; water content 76.25-84.52% (wb), ash content 6.55-7.13% (db), fat content 0.20-1.65% (db), protein content 2.67-9.63% (db), and carbohydrate 63.7-70.25% (db). The content of TSS, vitamin C, protein, and carbohydrate showed significant differences between fruit.